High grain quality accessions within a maize drought tolerant core collection - Dragana Ignjatovic-Micic (Scientia Agricola, 2014)
Maize (Zea mays L.) landraces are an important source of genes for improving commercial germplasm. Today, drought tolerance and grain quality are major challenges in maize cultivation due to climatic changes and population growth. The Maize Research Institute genebank has a drought tolerant collection, which includes 13 landraces (from the former Yugoslavia) and 12 introduced populations (from different countries). These accessions were analyzed for protein, oil, starch and tryptophan contents, in order to identify drought tolerant accessions with high grain quality. Also, simple sequence repeat (SSR) analysis with specific primers for opaque2 recessive allele (o2) was carried out. All analyzed accessions showed high levels of protein. Oil content ranged from 3.75 % to 5.40 % and starch content from 67.5 % to 71.30 %. Average protein content was not different (p < 0.01) between landraces and introduced populations. Starch and oil contents were higher in introduced populations at 0.84 % and 0.39 %, respectively (p < 0.01). Twenty-three accessions had high levels of tryptophan content. A high percentage of kernel type 1 and 2 indicated the presence of endosperm hardness modifier genes. Recessive o2 allele was found in most of the accessions. Absence of o2 in some high tryptophan accessions indicated action of another mutation. In two high tryptophan accessions an unknown band was detected. Absence of negative correlations between proteins, tryptophan and oil makes certain accessions suitable for use in the simultaneous improvement of target genotypes for these traits. Identified drought tolerant, high quality accessions can be used in breeding programs aimed at nutritional improvement of maize grown under drought conditions.